Peasant’s Movement Communication Strategies (Virtual Ethnography Study of Instagram Account @jogja_darurat_agraria) - Aprilianti Pratiwi; Sarwititi Sarwoprasodjo; Endriatmo Soetarto; Nurmala K. Pandjaitan (Jurnal Pekommas, 2019)
Issue of land grabbing and its relevation, such as violence, discrimination and criminalization of peasents, often escapes from the mainstream of the media. For this reason, a strategy is needed to make the people become aware of the issue of land grabbing. So far the strategy that has been done by activists, academics and related parties to defend the peasents who have been violence, discriminated and criminalized with conventionally. The purpose of this study is to analyze the communication strategies of peasant resistance movements on social media. The method used in this study is virtual etnography with participatory online observation techniques through two stages; studying and carrying out details the object. The researcher doing online partisipatif observation to the Instagram accounts @jogja_darurat_agraria by identifying elements of: communicators, communicants, messages, media, and effects. The results showed that the account already has carried out a well strategy communication, so that their ideological message well deliver to the communicant. The online activism of the peasant movement is the first step to mobilize the people to move in real terms.